Unraveling the Links Between the Initiation of Ventilation and Brain Injury in Preterm Infants - Barton, Samantha K.; Tolcos, Mary; Miller, Suzie L.; Roehr, Charles C.; Schmölzer, Georg M.; Davis, Peter G.; Moss, Timothy J. M.; LaRosa, Domenic A.; Hooper, Stuart B.; Polglase, Graeme R. (Frontiers in Pediatrics, 2015)
The initiation of ventilation in the delivery room is one of the most important but least controlled interventions a preterm infant will face. Tidal volumes (VT) used in the neonatal intensive care unit are carefully measured and adjusted. However, the VTs that an infant receives during resuscitation are usually unmonitored and highly variable. Inappropriate VTs delivered to preterm infants during respiratory support substantially increase the risk of injury and inflammation to the lungs and brain. These may cause cerebral blood flow instability and initiate a cerebral inflammatory cascade. The two pathways increase the risk of brain injury and potential life-long adverse neurodevelopmental outcomes. The employment of new technologies, including respiratory function monitors, can improve and guide the optimal delivery of VTs and reduce confounders such as leak. Better respiratory support in the delivery room has the potential to improve both respiratory and neurological outcomes in this vulnerable population.